Isolation and Identification of Sulphur Oxidizing Bacteria from Freshwater Fish Farm Soil - Kumar, N. Ranjit; Archana, K. K.; Basha, K. A.; Muthulakshmi, T.; Joseph, T. C.; Prasad, M. M. (Fishery Technology, 2018)
Sulphur oxidizing bacteria (SOB) are natural microflorain aquaculture farms that play a significant rolein sulphur cycle. In this study isolation, characterizationand sulphate ion production ability wascarried out to assess the role of SOB in utilizingthiosulphate. Ninety six distinct morphologicalisolates of SOB were isolated from the freshwaterfish farm soil employing six different isolationmedia. Subsequent dye reduction test revealed that16 isolates on Thiobacillus aquaesulis medium, 12isolates on T. denitrificans medium, 9 isolates on T.thioparus medium and 10 isolates on Thiothrixmedium showed characteristic color change of thedye (bromo phenol blue). Eight sulphur oxidizingbacterial isolates (SOBA17, SOBA12, SOBA3,SOBA20, SOBD10, SOBD16, SOBD12 and SOBD14)were selected for further studies based on the pHreduction test. To screen the potential sulphuroxidising bacteria, medium was amended withsodium thiosulphate and the sulphate ion productionability of the isolates was measured spectrophotometrically.Bacterial isolate of SOBA17 (1.62 mgml-1) showed maximum sulphate ion production,followed by SOBA20 (1.50 mg ml-1). The 16S rRNAsequencing revealed that the isolates belonged toThiobacillus aquaesulis. The partially purified sulphuroxidase of SOBA17 in SDS-PAGE exhibited threeconsecutive protein bands of molecular weight 10,17 and 30 kDa. The present study revealed that SOBhas the capacity to utilize sulphur in its oxidizedstate to non-toxic sulphate. Further studies areneeded to understand the diversity and role of thesebacteria in sulphur dynamics in aquaculture farms.